A Simple Simulation of Surface Plasmon Resonance in The Kretschmann Configuration Using Google Sheets - Quang, N. K.; Anh, N. P. Q.; Hieu, H. C. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2020)
This article describes a simple numerical simulation of three-layer surface plasmon resonance (SPR) in the Kretschmann configuration. The calculation was performed in Google Sheets, a web-based spreadsheet environment that functions similarly to Microsoft Excel where it is easily accessible for students via the internet. Specifically, Fresnel’s equations were utilized to calculate the intensity of the reflected light for the p-polarized incident light on a three-layer system. The complex functions were utilized to plot the SPR curves. We examined the change of the resonance angle by the influence of the incident wavelength. The simulation was also performed for different thicknesses of the gold film layer. To demonstrate the sensitivity, we obtained the SPR curves with the variation of the refractive index in the sensitive medium. The SPR accuracy was analysed by comparing our obtained result with the published work. It is intended to incorporate into undergraduate instrumental analysis courses.